GIVING OF LOW IMPACT AEROBIC GYMNASTICS AT AISIYAH ELDERLY BOARDING SCHOOL BRANCH, PEKALONGAN REGENCY TO IMPROVE PHYSICAL FITNES - Helmi Fatinabila (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail:, 2023)
One of the community service activities is through the Implementation of Low Impact Aerobic Gymnastics at the Aissiyah Elderly Islamic Boarding School, Pekalongan Regency Branch to Improve Physical Fitness. This activity was carried out on Saturday morning where the activities of the Aissiyah elderly boarding school were carried out. With the support and enthusiasm of the participants of our Aisyiyah boarding school for the elderly, there were 5 students with provisions from the campus, thank God, in giving aerobics to the elderly, they were able to run smoothly and full of joy. In the service team, which consists of 5 people, they have their respective duties, including as instructors and guards. In this activity the elderly followed the movements well and were full of enthusiasm, although some of them did the movements sitting down because they were unable to stand for long. In this implementation, we were warmly welcomed by the elderly participants and the board of senior boarding school activities, this also made us as servants excited after seeing the spirit of the elderly, even though they are getting older, they still have a youthful spirit to stay healthy and fit. and always enthusiastic in participating in pesantren activities and community service activities.